Ergonomiskt monteringsverktyg för arbete i renrum - Berghel, Magnus; Lindh, Agust; Pedersen, Elias; Steén, Jakob; Östman, Rasmus (My University, 2024)
The following report describes the results of a product development project commissioned by Metenova AB. The project’s goal was to create an assembly solution that improves the installation and removal of drive units on mixing tanks in cleanrooms, with a focus on ergonomics and efficiency. To identify user needs and requirements for the product, a preliminary study was conducted, including interviews, observations and information gathering. Using ergonomic analyses and methods for idea generation, concept development, and concept selection, a final concept was developed that meets the identified needs and requirements. The result is a mounting tool which is used in conjunction with a lift table. The product facilitates the mounting of the drive unit onto the mixing tank by maintaining the drive unit at the correct angle and height while allowing rotation to align the drive unit mounting holes with the tank plate. The product consists of an adapter mounted on the drive unit and a lift tablemounted structure with an axle to which the adapter is attached. The mounting tool is expected to reduce work-related injuries and required man-hours during installation, making it a valuable product for Metenova and their customers.